Health belief model to predict sharps injuries among health care workers at first level care facilities in rural Pakistan12. Issue 4 (19th September 2012) - Yousafzai, Mohammad Tahir; Siddiqui, Amna Rehana; Janjua, Naveed Zafar
Abstract Background We assessed the frequency and predictors of sharp injuries (SIs) among health care workers (HCWs) at first level care facilities (FLCF) in rural Pakistan. Method HCWs working at public clinic (PC), privately owned licensed practitioners' clinic (LPC) and non‐licensed practitioners' clinic(NLC) were interviewed on universal precautions (UPs) and constructs of health belief model (HBM) to assess their association with SIs through negative‐binomial regression. Results From 365 clinics, 485 HCWs were interviewed. Overall annual rate of SIs was 192/100 HCWs/year; 78/100 HCWs among licensed prescribers, 191/100 HCWs among non‐licensed prescribers, 248/100 HCWs among qualified assistants, and 321/100 HCWs among non‐qualified assistants. Increasing knowledge score about bloodborne pathogens (BBPs) transmission (rate‐ratio (RR): 0.93; 95%CI: 0.89–0.96), fewer years of work experience, being a non‐licensed prescriber (RR: 2.02; 95%CI: 1.36–2.98) licensed (RR: 2.86; 9%CI: 1.81–4.51) or non‐licensed assistant (RR: 2.78; 95%CI: 1.72–4.47) compared to a licensed prescriber, perceived barriers (RR: 1.06; 95%CI: 1.03–1.08), and compliance with UPs scores (RR: 0.93; 95%CI: 0.87–0.97) were significant predictors of SIs. Conclusion Improved knowledge about BBPs, compliance with UPs and reduced barriers to follow UPs could reduce SIs to HCWs. Am. J. Ind. Med. 56:479–487, 2013. © 2012 Wiley Periodicals, Inc.